The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1037/1076-898x.1.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Object versus space-based models of visual attention: Implications for the design of head-up displays.

Abstract: Thirty-two pilots flew instrument approaches in a high-fidelity simulator, first inside and then outside of the clouds. They used 2 symbology sets, presenting flight guidance information that was either conformal or nonconformal with the background. Half of the trials presented the symbology in a head-up location, and half presented the symbology head-down. Airspeed tracking was displayed with nonconformal digital symbology. An unexpected far domain event was presented on 1 trial per pilot. For flightpath cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 16 publications
6
108
2
Order By: Relevance
“…This hypothesis is based on the findings regarding the problems of low salience of rare event detection with the superimposed imagery, characteristic of head-up displays (Martin-Emerson & Wickens, 1997;Wickens & Long, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is based on the findings regarding the problems of low salience of rare event detection with the superimposed imagery, characteristic of head-up displays (Martin-Emerson & Wickens, 1997;Wickens & Long, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However in the head down position, it appears less "natural" and direct, and requires a greater degree of cognitive transformation, to use the cue to identify a direct position in space. Indeed in the HUD research, we have found that the benefits of conformal cueing (locating the runway) are considerably enhanced when presented in a head up, rather than at a head down location (Wickens & Long, 1995;Fadden & Wickens, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty dividing attention between two sources of information presented by overlapping imagery has been examined extensively in the HUD and HMD domains and is represented in the cases in which the symbology presented in the forward field of view captures the pilots' attention at the cost of processing other information in the far domain beyond the symbology, i.e., attentional tunneling (Fadden et al, 1998;Larish & Wickens, 1991;MartinEmerson & Wickens, 1992McCann et al, 1992;National Research Council, 1997;Sampson, 1993;Wickens & Long, 1995). This miscalibration in attention may be a consequence of emphasizing certain display features [e.g., superimposing guidance symbology as in Ververs and Wickens (1998a)] such that operators overutilize the information provided by the system, which allows performance of the task with less cognitive effort.…”
Section: Divided Attentionmentioning
confidence: 99%
“…In fact, Dopping-Hepenstal (1981) noted that military pilots fixated more frequently on information presented on a HUD at the cost of scanning the outside scene but at the same time were more confident in their abilities. Fadden et al (1998) conducted a meta-analysis of research that has compared the use of head-up versus head-down displays in air and ground vehicles and found that as more information is added to the HUD, there is a cost in detecting events in the world (e.g., noticing the presence of an airplane on the runway during a landing task) relative to the head-down display, particularly if these events are unexpected and not salient (Larish & Wickens, 1991;Wickens & Long, 1995;Wickens, 1997).…”
Section: Divided Attentionmentioning
confidence: 99%
See 1 more Smart Citation